Osteochondral Lesions of the Talus – A Biomechanical Explanation for Larger OLT Shoulder Lesions Leading to Increased Patient Risk. Issue 4 (16th October 2019) - Lawson, Peter; Kumparatana, Pam; Baldini, Todd; Challa, Shanthan; Moon, Daniel; Hunt, Kenneth
Category: Ankle, Trauma Introduction/Purpose: Osteochondral lesions of the talus (OLT) are a common injury that can result in pain, disability, and risk ankle degeneration, with poor outcomes when not managed properly. Unconstrained 'shoulder' lesions on the medial edge of the talar dome present a particular challenge. The objective of this study was to assess the effect of increasing size of a medial OLT shoulder lesion on ankle joint contact mechanics and to determine a threshold size that would warrant bulk grafting of the defect. Our hypothesis is that larger defects will demonstrate increased pressure applied over a lesser surface area, with peak pressure progressing towards the rim of the defect, resulting in an increased risk for tissue damage and need for treatment. Methods: Nine cadaver ankle joints were dissected without disrupting the medial and lateral stabilizing ligaments. A Tekscan pressure sensor was inserted into the ankle joint. Intact specimens were axially compressed up to 800 N with the foot in neutral and again at 20° inversion, simulating ankle position during inversion injury. The specimens were then tested with progressively larger semicircular osteochondral lesions at diameters of 8, 10, 12, 14, and 16 mm that were centered on the edge of the medial talar dome, followed by a final ovoid lesion of 16x20 mm. After each lesion was created the specimens were retested. Linear mixed models adjusted for donor characteristics and assessed changes in peak pressure (MPa), contact area (mm2), peak pressure location (mm), and distance from peak pressure location to the lateral rim of the defect (mm) by defect size and ankle position. Results: For all defect sizes, mean peak pressures were significantly higher in inversion compared to neutral. Mean peak pressure magnitude progressively increased with defect size in both ankle positions. Donor characteristics did not significantly affect mean peak pressure. Contact area decreased in both positions as defect size increased, but inversion led to significantly lower contact areas than in neutral. In neutral positions, the location of peak pressure moved laterally on the talar dome but also moved closer to the defect rim as the size of the defect increased. The rim-peak pressure distance stabilized for defect sizes of 10 mm and above. In inversion, however, the rim-peak pressure distance remained unchanged at about 8 mm for all defect sizes. Conclusion: As OLT defect sizes increased, we observed an increase in peak pressure, a decrease in contact surface area, and a lateral translation of peak pressure location relative to the defect rim. Distance between location of peak pressure and defect rim decreased with neutral loading until a 10 mm defect but remained consistent in inversion loading. These findings suggest a biomechanical explanation for secondary injuries and treatment failures in larger OLT shoulder lesions due to maladaptive cartilage tissue on the dome of the talus. Larger defects (=10 mm) remain a critical point of interest with predictive clinical value for OLT outcomes.